Educational dynamics and practices in diverse contexts: A comparative study between Brazil and Portugal - Porto, Joel Augusto Moura; Guedes, Ronaldo Santos; de Freitas, Rita de Cássia Ramos Queiroz; da Silva, Lília Raquel Fé; Coutinho, Mateus Lima; Rocha, Vivianne Cambuí Figueiredo (Seven Editora, 2024)
This chapter provides a comparative analysis of educational institutions in Brazil and Portugal, focusing on practical observations from on-site visits. Highlighting the transformative role of teaching internships, the study explores how these experiences enrich both interns and seasoned educators by fostering innovative teaching practices. In Portugal, we examined the Music Conservatory of Coimbra, Avelar Brotero Secondary School, and Infanta Dona Maria Secondary School. The Music Conservatory, founded in 1986, exemplifies inclusive music education with specialized teachers and facilities designed for optimal learning environments. Avelar Brotero Secondary School offers diverse courses and vocational training, emphasizing practical learning and international educational exchanges. Infanta Dona Maria Secondary School, established in 1918, stands out for its rigorous academic standards and comprehensive facilities, supporting students with diverse needs and promoting environmental awareness. In Brazil, we focused on the State Polyvalent School of Amaralina in Salvador, established in 1973 under the PREMEN program. Despite its location in a challenging neighborhood, the school provides a nurturing environment with modern facilities, practical workshops, and inclusive educational programs. This comparative exploration offers valuable insights into educational dynamics, infrastructure, and cultural impacts in Brazil and Portugal, contributing to a deeper understanding of effective educational practices within diverse global contexts. DOI:https://doi.org/10.56238/sevened2024.014-028